2008
DOI: 10.1002/path.2403
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of immune granuloma formation in a Leishmania braziliensis‐induced self‐limiting cutaneous infection in the primate Macaca mulatta

Abstract: In order to unravel the physiopathology of leishmaniasis in humans, it is necessary to better understand how Leishmania are able to survive for years within immunologically active granulomas. In the present study, we used a macaque (Macaca mulatta) model of infection with Leishmania braziliensis as a means of assessing the usefulness of this primate system. This model more closely mirrors human protective immunity to Leishmania than the murine model; therefore, we used it to study the host inflammatory granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Amastigote-laden neutrophils have been isolated from numerous infected hosts, including experimentally infected macaques and naturally infected humans, dogs, and foxes (17,(19)(20)(21). However, the immunological ramifications of amastigote-neutrophil interactions remain largely uncharacterized.…”
mentioning
confidence: 99%
“…Amastigote-laden neutrophils have been isolated from numerous infected hosts, including experimentally infected macaques and naturally infected humans, dogs, and foxes (17,(19)(20)(21). However, the immunological ramifications of amastigote-neutrophil interactions remain largely uncharacterized.…”
mentioning
confidence: 99%
“…In L. amazonensis-infected macaques it was demonstrated that CD4 + /CD8 + T-cell ratios favour CD8 + cells in both active and healing skin lesions (Amaral et al 2000). A more marked variation in the clinical course of infection was found when groups of macaques were inoculated with different Leishmania braziliensis strains (Teva et al 2003, Souza-Lemos et al 2008. The inocula produced lesions of variable severity, ranging from localized self-healing CL to nonhealing disease (Figs 3A, C).…”
Section: Natural and Experimental Leishmanial Infections In Nhpmentioning
confidence: 96%
“…Pathological findings included a typical cell-mediated immunity-induced granulomatous reaction (Fig. 3D), which consisted of all cell types found within human granulomas, including the presence of both IFN-γ-or TNF-α-producing CD4 + and CD8 + T-cells, as well as IL-10-producing CD4 + CD25 + T-cells (Souza-Lemos et al 2008). While several groups have described that ML (mucosa lesions) has not been observed in Neotropical monkey models of CL (Lainson & Shaw 1977, Lujan et al 1986a, Cuba Cuba et al 1990, in our own studies (Teva et al 2003, G Grimaldi Jr, unpublished data) two of 30 (6.7%) L. braziliensis-infected macaques developed nasal ML (Fig.…”
Section: Natural and Experimental Leishmanial Infections In Nhpmentioning
confidence: 99%
See 2 more Smart Citations